First Colombian consensus on congenital Chagas and clinical approach for women of child-bearing age diagnosed with Chagas - Zulma M. Cucunubá; Carlos A. Valencia-Hernández; Concepción J. Puerta; Sergio Sosa-Estani; Faustino Torrico; Jorge Alberto Cortés; Juan David Ramirez; Mauricio J. Vera; Belkis Xiomara Acosta; Carlos Arturo Álvarez; Edith Ángel Muller; Mauricio Beltrán; et al.
Abstract Congenital transmission of Chagas disease has not been extensively studied in Colombia, and there are no standardized processes in the health system regarding the specific diagnosis, treatment and follow-up of this disease. To generate recommendations on congenital Chagas disease and Chagas in women of childbearing age in Colombia, a consensus of experts was developed. An extensive literature search through the Medline database was carried out using the MeSH terms: «Chagas disease/congenital», «prevention and control», «diagnosis», «therapeutics» and «pregnancy». Appropriate abstracts were selected and the full texts were analyzed. The relevant information was synthesized, classified, and organized into tables and figures and was presented to a panel of experts, which was composed of 30 professionals from various fields. Based on the Delphi methodology, three rounds of consultation were conducted. The first and second rounds were based on electronic questionnaires that measured the level of consensus of each question among the participants. The third round was based on a face-to-face discussion focusing on those questions without consensus in the previous consultations. The evidence was adapted to national circumstances on a case-by-case basis, and the content the final document was approved. These recommendations are proposed for use in routine medical practice by health professionals in Colombia.